STEM Tomography of Au Helical Assemblies. (June 2022) - Sobczak, Kamil; Turczyniak-Surdacka, Sylwia; Lewandowski, Wiktor; Baginski, Maciej; Tupikowska, Martyna; González-Rubio, Guillermo; Wójcik, Michał; Carlsson, Anna; Donten, Mikołaj
Abstract: Abstract : Composite, helical nanostructures formed using cooperative interactions of liquid crystals and Au nanoparticles were studied using a scanning transmission electron microscopy (STEM) mode. The investigated helical assemblies exhibit long-range hierarchical order across length scales, as a result of the crystallization (freezing) directed growth mechanism of nanoparticle-coated twisted nanoribbons and their ability to form organized bundles. Here, STEM methods were used to reproduce the 3D structure of the Au nanoparticle double helix.